Tuning the ferroelectric properties of trialkylbenzene-1,3,5-tricarboxamide (BTA) - Urbanavičiūtė, Indrė; Meng, Xiao; Cornelissen, Tim D.; Gorbunov, Andrey V.; Bhattacharjee, Subham; Sijbesma, Rint P.; Kemerink, Martijn (Advanced electronic materials, 2017)
This study demonstrates how simple structural modification of a prototypical organic ferroelectric molecule can be used to tune its key ferroelectric properties. In particular, it is found that shortening the alkyl chain length of trialkylbenzene-1,3,5-tricarboxamide (BTA) from C18H37 to C6H13 causes an increase in depolarization activation energy (≈1.1-1.55 eV), coercive field (≈25-40 V µm−1), and remnant polarization (≈20-70 mC m−2). As the polarization enhancement far exceeds the geometrically expected factor, these observations are attributed to an increase in the intercolumnar interaction. The combination of the mentioned characteristics results in a record polarization retention time of close to three months at room temperature for capacitor devices of the material having the shortest alkyl chain. The long retention and the remnant polarization that is as high as that of P(VDF:TrFE) distinguish the BTA-C6 material from other small molecular organic ferroelectrics and make it a perspective choice for applications that require cheap, flexible, and lightweight ferroelectrics.